Intervensi Aktivitas Fisik Berbasis Komunitas terhadap Kesejahteraan Psikologis: Tinjauan Literatur Sistematis - Fifi Nafsiyatun Nurul Fadlilah; Fajar Awang Irawang; Adi S (Universitas Hamzanwadi, 2026)
This study aims to identify, evaluate, and synthesize empirical evidence regarding the effects of community-based physical activity interventions on psychological well-being. This study employed a systematic literature review method in accordance with the PRISMA guidelines. Articles were searched in the Scopus, PubMed, Web of Science, and Google Scholar databases from 2015 to 2026 using keywords related to group exercise, community exercise, and mental health. Article quality was assessed using the JBI Checklist and CASP instruments. Of the 57 articles identified, 7 met the inclusion criteria and were analyzed further. The review results indicate that community-based physical activity interventions consistently have a positive impact on psychological well-being, including improvements in quality of life, self-efficacy, and emotional regulation, as well as reductions in stress and negative mental health symptoms. These benefits arise through three mechanisms: physiological (improved fitness and neurobiological regulation), psychological (increased self-confidence and coping skills), and social (community support and reduced loneliness). Key factors contributing to the program’s success include social interaction, community support, flexibility in exercise intensity, cultural adaptation, program sustainability, and the role of professional facilitators. These findings confirm that community-based physical activity is not only beneficial for physical health but also effective in improving overall psychological well-being.